Design of acoustic foam wedge panels by finite element frequency domain acoustical analysis. (May 2019) - Tsay, Huoy-Shyi; Yeh, Fung-Huei
Acoustic foam wedge panels provide good sound absorption qualities in the mid and high frequency ranges. In this study, a finite element frequency domain acoustical analysis is used for analysis. Such a numerical method is more efficient than the earlier studies by saving the calculation time on the elements of the incident acoustic field. During the design of a wedge panel, the cross-sectional width and the area of one section of the wedge panel are kept the same throughout the study. By varying the wedge angle, the maximum sound absorption capability of the wedge foam can be found. It is concluded that in the interested frequency regions, 100–4000 and 2000–4000 Hz, the wedge foam with wedge angle of 31° has the excellent sound absorption capability.